Distribution of heavy metal concentrations in the different soft and hard tissues of tropical mud-flat snail telescopium telescopium (Family: Potamididae) collected from Sepang Besar River - Yap, Chee Kong; Arifin, Noorhaidah (Universiti Putra Malaysia Press, 2012)
The concentrations of Cd, Cu, Pb, Fe, Ni and Zn were determined in the different parts of the soft tissues (foot, cephalic tentacle, mantle, muscle, gill, digestive caecum and remaining soft tissues) and three parts of hard tissues or shells (anterior shell, middle shell and posterior shell) of the mud-flat snail Telescopium telescopium collected from Sepang Besar River. From the cluster analysis, the dendrogram shows that the three parts of the shells are clustered separately from the different parts of the soft tissues, indicating different mechanisms and strategies of metal accumulation and regulation of heavy metals in the shells from the different soft tissues. Among the different soft tissues, the dendrogram also shows that the digestive caecum is clustered differently from other soft tissues, indicating that this organ is distinctly high in metal accumulation and this may probably suggest a different route of metal sequestration from the rest of the soft tissues. The metal distribution found in the different soft tissues of T. telescopium is an important knowledge in establishing this mud-flat gastropod as a promising biomonitor of metal contamination and bioavailability for the intertidal area of Peninsular Malaysia.